Keputusan Pembelian UMKM: Peran Digital Marketing dan Brand Image (Studi Kasus: UMKM Maja Lebak, Banten) - Wenty Febrianti; Ahmad Darda (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The development of digital technology encourages Micro, Small, and Medium Enterprises (MSMEs) to adapt their marketing strategies to improve their competitiveness and consumer purchasing decisions. This study aims to analyze the influence of digital marketing and brand image on MSME product purchasing decisions in Maja District, Lebak Regency, Banten. The research method used is a survey method with a descriptive and causal approach. Data were collected through questionnaires to 63 MSMEs from a total population of 70 MSMEs with probability sampling techniques. Data analysis was carried out using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method through reflective indicators in the SmartPLS 4 application. The results showed that digital marketing had no and insignificant effect on purchasing decisions, with a path coefficient value of -0.209 and a t-statistic value of 0.902 (<1.96). In contrast, brand image has a positive and significant effect on purchasing decisions, with a path coefficient of 0.388 and a t-statistic of 3.528 (> 1.96). This finding indicates that purchasing decisions for MSME products in Maja District are more influenced by consumer perceptions of brand image than by digital marketing activities. The managerial implications of this study emphasize the importance of strengthening brand image as a primary strategy in improving purchasing decisions, as well as the need to evaluate and optimize the implementation of digital marketing to be more effective and oriented towards building brand image. This study is expected to serve as a reference for MSME actors and future researchers in developing digital-based MSME marketing strategies.